Status of Tropospheric Ozone and Other Primary Air Pollutants After The Implementation of CNG in Delhi - Saxena, Pallavi; Ghosh, Chirashree (Asian Journal of Chemistry, 2010)
This paper estimates the status of air pollutants (primary pollutants and one of the secondary pollutant-tropospheric ozone) in Delhi after mandating the use of compressed natural gas (CNG). The objective of our study has two issues-whether CNG conversion has impinged on the primary pollutants and tropospheric ozone pollution profile or whether the physiography, climate and major emission sources are responsible factors for spatial pattern of pollution in Delhi. To carry out the analysis, daily ambient air quality secondary data of NOx, SOx, CO, SPM and RSPM (Jan 2002-Dec 2006, ITO crossing; Source-Central Pollution Control Board, Delhi) was used. Besides this secondary pollutant (ozone) and meteorological data's (Jan 2002-Dec 2006, Lodhi Road; Source-India Meteorological Department, Delhi) were also collected and analyzed. The results however, do not indicate an all round improvement in ambient air quality of Delhi. Except SO2 all primary air pollutants (NO2, SPM, RSPM and CO) are increasing from the last five years (2002-2006) at Site- I (ITO) and ozone concentration was reported to be increasing from 2002-2006 at Site-II (Lodhi Road) as well as at Site-I (ITO). Moreover, the concentration of ozone was higher at Site-I than at Site-II in all the reported years.